L'évaluation de la culture scientifique des élèves français de quinze ans dans PISA 2009 - Nicolas Coppens (Nantes Université, 2012)
The following article shortly presents the international survey PISA, conducted by the OECD, and which, in 2009, examined 15-year-old students' performance in science, reading and mathematics in 65 different countries. It then describes the scientific literacy as it is defined in PISA before analyzing French pupils' results in this field.